IMPLEMENTATION OF THE TWO-DIMENSIONAL FOURIER TRANSFORM FOR ANALYSIS OF SPIRAL STRUCTURES IN GALAXIES - Faria Costa, Stella (2023)
Normal spiral galaxies have a nucleus, disk, bulge, halo, and spiral arms. These systems arouse a lot of curiosity, attraction, and scientific questions and, consequently, many studies and techniques are proposed for the analysis of such structures. In this work, we implement the two-dimensional Fourier Transform method to analyze the spiral structures of galaxies and for that, a Python program was developed. The algorithm was tested using three images: a two-armed logarithmic spiral, a three-armed logarithmic spiral, and an image of the galaxy NGC 4321. With this technique we were able to determine the dominant components in each of the spiral structures, being m=2, m=3 and e m=2, respectively.